Algorithm-Driven Pharmacological Management of Bipolar Disorder in Connecticut Prisons. (February 2013) - Kamath, Jayesh; Zhang, Wanli; Kesten, Karen; Wakai, Sara; Shelton, Deborah; Trestman, Robert
The objective of this study was to assess adaptation of the Texas Implementation of Medication Algorithm (TIMA) for bipolar disorder (BD) in the Connecticut Department of Correction. A nonrandomized sample of 20 males and 20 females, with diagnoses of BD Type I or II, was enrolled in the study. Two TIMA-trained psychiatrists treated the participants over a 12-week period following the TIMA protocol. The primary outcome measure was the Bipolar Disorder Symptom Scale. Secondary outcome measures evaluated global clinical status, comorbid symptomatology, and quality of life. Significant improvement was seen with the primary and secondary outcome measures ( p < .001). Subanalyses showed differences in outcomes based on gender and whether a manic or depression algorithm was used. Antidepressant and antipsychotic medication use decreased, with increase in anticonvulsant and anxiolytic medication usage. This pilot study confirmed the effectiveness and benefits of TIMA for BD adaptation in the correctional setting.